Meningkatkan Kemampuan Berpikir Kritis Melalui Problem Posing - Widha Nur Shanti; Dyahsih Alin Sholihah; Adhetia Martyanti (LITERASI (Jurnal Ilmu Pendidikan), 2017)
This study aims to explain how the problem posing approach adopted in the study of mathematics can develop students' critical thinking skills. The method used in this research is literature study (library research). The data in this study is a secondary data such as the results of the research as scientific books, scientific journals, research reports, and other relevant sources. Data analysis techniques in the study include three stages, namely organize, synthesize, and identify.These results showed that the problem posing approach to the stages of learning, among others (1) create a situation of mathematics; (2) create a mathematical question; (3) solve math problem; (4) to apply mathematics, has relevance to the indicators on critical thinking skills, which include interpretation, analysis, evaluation, and decision. Overall, it was concluded that the students' critical thinking skills can be improved by the application of problem posing approach in the learning process.